A Comparison of Silicon and Silicon Carbide MOSFET Switching Characteristics - Ong, A.; Carr, J.; Balda, J.; Mantooth, A. (2007 IEEE Region 5 Technical Conference, 2007)
Silicon carbide (SiC) is a wide-bandgap semiconductor material that has several promising properties for use in power electronics applications. While SiC manufacturing techniques are still being researched, several SiC devices such as SiC Schottky diodes have entered the market and are finding utility in numerous applications. In this paper, a new 1200 V, 10 A SiC MOSFET will be compared to 1000 V, 10 A Si MOSFET in terms of their dc and transient characteristics and their switching performance in a step-down converter. The SiC device compares favorably to the Si device tested as well as other Si devices available on the market for a similar voltage range.